The motor testing system design based on SINAMICS S120 inverter - Zhengtang, Liu; Xiangdong, Li; Lin, Zhang (Journal of physics. Conference series, 2020)
In this paper, an induction motor testing system based on Sinamics S120 inverter is designed and implemented. This system adopts Siemens S7-300 programmable controller as the main control unit, and the Sinamics S120 inverter as the actuator of the companion and subject motors. Because the whole working process is fully automatic controlled by PLC, it has high working reliability. All inverters on one DC generatrix decrease power consumption and have remarkable energy-saving effect and practical value.